DAMPAK PERIKLANAN YANG INFORMATIF TERHADAP KEPUTUSAN PEMBELIAN PRODUK SABUN MANDI - Suharno, Rizki Adi Anggoro; Dirgantara, I Made Bayu (Diponegoro Journal of Management, 2018)
This  research  was  conducted  to  test  and  analyze  causal  relationship  between Informational Advertising to Consumer Purchase Decision of Toiletries Product, Soap. The  aim  of  this  research  is  also  to  analyze  the  difference  of  information  given  by advertising to consumer purchase decision of soap product, whether the information of soap  product  that  have  been  given  to  the  participants can  influence  the  relationship between informational advertising with consumer purchase decision of soap product.The  method  used  in  this  research  is true  experimental  design  with  laboratory experiment. The number of participants used was 30 participants, consisting of 15 participants for the experiment group that received the information of the soap product and 15 participants for the control group who did not get the information of the soap product.  The  data  analysis  tests used  in  this research  are  Paired  Sample  T-test  and Independent  Sample  T-test  in  order  to  know  the  difference  and  compare  the  results between the experimental research groups.The result of the analysis with t-test shows that experiment done successfully. T-test shows that there is a difference in purchase decision of the participant just right before and after treatment with product information applied. The statistical result showed that H1 is  accepted.  The  statistical  result  also  showed  that  soap  information  that  participant received through an advertisement is capable in providing information needed by the participant to consider and decide their purchase decision about the soap product.